Measuring spatial and temporal trends of nicotine and alcohol consumption in Australia using wastewater‐based epidemiology. (26th February 2018) - Lai, Foon Yin; Gartner, Coral; Hall, Wayne; Carter, Steve; O'Brien, Jake; Tscharke, Benjamin J.; Been, Frederic; Gerber, Cobus; White, Jason; Thai, Phong; Bruno, Raimondo; Prichard, Jeremy; et al.
Abstract: Background and aims: Tobacco and alcohol consumption remain priority public health issues world‐wide. As participation in population‐based surveys has fallen, it is increasingly challenging to estimate accurately the prevalence of alcohol and tobacco use. Wastewater‐based epidemiology (WBE) is an alternative approach for estimating substance use at the population level that does not rely upon survey participation. This study examined spatio‐temporal patterns in nicotine (a proxy for tobacco) and alcohol consumption in the Australian population via WBE. Methods: Daily wastewater samples ( n  = 164) were collected at 18 selected wastewater treatment plants across Australia, covering approximately 45% of the total population. Nicotine and alcohol metabolites in the samples were measured using liquid chromatography–tandem mass spectrometry. Daily consumption of nicotine and alcohol and its associated uncertainty were computed using Monte Carlo simulations. Nation‐wide daily average and weekly consumption of these two substances were extrapolated using ordinary least squares and mixed‐effect models. Findings: Nicotine and alcohol consumption was observed in all communities. Consumption of these substances in rural towns was three to four times higher than in urban communities. The spatial consumption pattern of these substances was consistent across the monitoring periods in 2014–15. Nicotine metabolites significantly reduced by 14–25% ( P  = 0.001–0.008) (2014–15) in some catchments. Alcohol consumption remained constant over the studied periods. Strong weekly consumption patterns were observed for alcohol but not nicotine. Nation‐wide, the daily average consumption per person (aged 15–79 years) was estimated at approximately 2.5 cigarettes and 1.3–2.0 standard drinks (weekday–weekend) of alcohol. These estimates were close to the sale figure and apparent consumption, respectively. Conclusions: Wastewater‐based epidemiology is a feasible method for objectively evaluating the geographic, temporal and weekly profiles of nicotine and alcohol consumption in different communities nationally.